2011
DOI: 10.1186/1471-2199-12-11
|View full text |Cite
|
Sign up to set email alerts
|

High throughput nano-liter RT-qPCR to classify soil contamination using a soil arthropod

Abstract: BackgroundTo incorporate genomics data into environmental assessments a mechanistic perspective of interactions between chemicals and induced biological processes needs to be developed. Since chemical compounds with structural similarity often induce comparable biological responses in exposed animals, gene expression signatures can serve as a starting point for the assessment of chemicals and their toxicity, but only when relevant and stable gene panels are available. To design such a panel, we isolated differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 62 publications
1
16
0
Order By: Relevance
“…16 A study by de Boer et al (2011) showed that multiple ABC transporters and copper pumps (copper-transporting ATPase 1, 2) were upregulated in response to cadmium toxicity. 43 In the present study, significantly induced metallothionein expression was found in F. candida exposed to either CuO or WCCo NMs and induction of the ABC transporter gene even persisted in animals after 2 recovery generations while in clean soil when previously exposed to WCCo-NM; all indicating a function in maintaining metal or redox homeostasis.…”
Section: Transcriptional Responses Associated With Multi-generation Csupporting
confidence: 52%
See 1 more Smart Citation
“…16 A study by de Boer et al (2011) showed that multiple ABC transporters and copper pumps (copper-transporting ATPase 1, 2) were upregulated in response to cadmium toxicity. 43 In the present study, significantly induced metallothionein expression was found in F. candida exposed to either CuO or WCCo NMs and induction of the ABC transporter gene even persisted in animals after 2 recovery generations while in clean soil when previously exposed to WCCo-NM; all indicating a function in maintaining metal or redox homeostasis.…”
Section: Transcriptional Responses Associated With Multi-generation Csupporting
confidence: 52%
“…A previous study showed that metal stress affects cell differentiation and adhesion in the basal lamina in human fibroblasts, where collagen and laminin production decreased upon low-dose exposure to silver and gold nanoparticles. 47 Laminin A gene expression was also affected in cadmium and phenanthrene exposed F. candida, irrespective of compound (De Boer et al 2011); 43 suggesting persistent differential gene expression as a result of metal stress. In the present study, a significant effect of the interaction History*Generation on gene expression was found in WCCo-NM exposed F. candida.…”
Section: Transcriptional Responses Associated With Multi-generation Cmentioning
confidence: 99%
“…Quantitative PCR (QPCR) was performed using a selected group of genes according to de Boer et al ( 2011b ) on a Biomark HD system (Fluidigm). Information on gene description and PCR primer sequence can be found in Table 2 of the results section.…”
Section: Methodsmentioning
confidence: 99%
“…Environmental stressors, such as insecticides, can activate many genes but down-regulate others in the collembolan F. candida (de Boer et al, 2011). In fact, differential regulation of genes is considered as an early warning sign of homeostasis disruption due to stress, since it precedes protein translation and metabolite biosynthesis in response to a changing environment.…”
Section: Introductionmentioning
confidence: 99%